Library collaborations and community partnerships : enhancing health and quality of life - Hines-Martin, Vicki; Cox, Fannie; Cunningham, Henry R. (Abingdon, Oxon ; New York, NY : Routledge, 2020)
Library Collaborations and Community Partnershipsillustrates the value of libraries and their resources through an array of alliances toimprove health and enhance people's lives. Itis unique in its illustration of key principles of collaboration, partner engagement, shared leadership, project development and outcomes measurement, as well as the challenges inherent in collaborations among diverse partners. The book includes collaboration exemplars focused on education, health, information literacy and capacity building forpopulations that experience access and resource disparities. It highlights the innovative use of existing assets, environments and diverse professions to broaden access to resources and information to those in need. The strategies, challenges, outcomes and lessons learned that are described in the volume have application for a variety of settings and populations. Highlighting the key role that libraries play in guiding successful interprofessional collaborations with communities, Library Collaborations and Community Partnerships should be of interest to academics, studentsandprofessionals engaged in library and information science, education, health care, social services and community organizations.
Section 1. Theoretical Foundations -- Introduction / Vicki Hines-Martin -- Unrecognized Roles of Libraries in Collaborations to Improve Communities History / Fannie Cox -- Interprofessional Practice and Collaboration / Vicki Hines-Martin -- Communities and Community Engagement / Henry R. Cunningham -- Section 2. Project Exemplars -- Information Literacy -- Education -- Health and Behavior -- Capacity Building -- Section 3. Perspective, Challenges, and Future Directions / Vicki Hines-Martin, Henry R. Cunningham, and Fannie Cox.
OCLC-licensed vendor bibliographic record.
Keywords: Libraries and community; Libraries and community -- United States; Libraries and community -- Case studies; Libraries and community -- United States -- Case studies; Libraries and society; Libraries and education; Library cooperation; Community leadership; Interprofessional relations; Public health; LANGUAGE ARTS & DISCIPLINES / Library & Information Science